The Impact of Permanent Pacemaker Implantation on the Quality of Life in Elderly Patients: A Scoping Review - Artha Artha; Muhamad Zulfatul A'la; Rondhianto Rondhianto (Indonesian Journal of Global Health Research, 2025)
The implantation of a permanent pacemaker has become a primary strategy for managing cardiac arrhythmias in elderly patients to enhance quality of life, reduce cardiovascular symptoms, and improve physiological function. While pacemakers have been proven effective in enhancing mobility, emotional well-being, and physical endurance, their impact varies among patients depending on health conditions, social support, and psychological readiness. Therefore, further exploration of the clinical and psychosocial implications of pacemaker implantation in elderly individuals is required. This scoping review aims to identify and analyze the impact of permanent pacemaker implantation on the quality of life of elderly patients, with a focus on patient safety, psychosocial adaptation, and implementation challenges.Methods: A systematic search was conducted in ScienceDirect, ProQuest, and PubMed to identify relevant articles published between January 2015 and December 2024. Out of 1,321 articles initially identified, 33 articles were selected for full-text review after applying inclusion and exclusion criteria. A critical appraisal using the Joanna Briggs Institute (JBI) framework determined that 9 articles met the final criteria for analysis. The studies included in this review involved elderly patients with pacemakers across various healthcare settings, including hospitals, outpatient clinics, and community healthcare services, to assess the impact of pacemakers on physical and mental well-being as well as patient satisfaction. Results: Pacemaker implantation generally improves the quality of life of elderly patients, particularly in terms of cardiovascular function, mobility, and independence. Additionally, pacemakers help reduce the risk of arrhythmia-related complications, enhance patient confidence, and improve adherence to medical therapy. However, several challenges persist, including post-implantation infection risks, psychosocial disturbances, and limited access to pacemaker technology in certain regions. The studies also identified research gaps, particularly in longitudinal evaluations of the impact of pacemakers on elderly patients with comorbidities and cognitive impairment.Conclusion: Pacemaker implantation is an effective intervention for improving the quality of life of elderly patients with cardiac arrhythmias. However, a more comprehensive patient-centered approach, including psychosocial support, pre-implantation education, and optimized post-procedural monitoring, is crucial. Further research is recommended to explore the long-term effects of pacemaker implantation and develop more adaptive care strategies for vulnerable elderly populations.